Risk factors for bladder calculi in patients with benign prostatic hyperplasia. Issue 32 (August 2017) - Huang, Wei; Cao, Jun-Jie; Cao, Min; Wu, Hong-Shen; Yang, Yong-Yi; Xu, Zi-Meng; Jin, Xiao-Dong
Abstract : Abstract: We aim to find the risk factors that influence the formation of bladder calculi in patients with benign prostate hyperplasia (BPH) and to reduce the surgical intervention related to bladder calculi. Between January 2015 and October 2016, 332 patients with BPH underwent surgical therapy were retrospectively evaluated. Patients with BPH were categorized into 2 groups: 94 patients with bladder calculi in group 1 and 238 patients without bladder calculi in group 2. Medical history, age, body mass index (BMI), total prostate specific antigen, total prostate volume (TPV), International Prostate Symptom Score (IPSS), intravesical prostatic protrusion (IPP), urodynamic parameters, and urine culture were compared between groups. There was no significant difference in the age, BMI, peak flow rate, and total IPSS between groups. TPV, total prostate specific antigen, and duration of BPH were significantly lower in group 1 than those in group 2. In addition, IPP was significantly higher in group 1 than group 2 ( P  < .001). Besides, after exclusion of patients with urinary retention and indwelling catheter, group 1 associated with a significantly higher preoperative positive rate of urine culture than that of group 2 ( P  = .046). Multivariate analysis indicated that IPP was a significant independent risk factor for the presence of bladder calculi. The incidence of bladder calculi in patients with BPH was proved to be closely associated with preoperative positive urine culture and longer IPP in our study. Furthermore, the IPP was presented to be an independent risk factor for the formation of bladder calculi. And early antibacterial therapy of urinary tract infection (UTI) may help to prevent the presence of bladder calculi in patients with BPH.